Exports and imports in the BOF4 quarterly model of the Finnish economy - Juha Tarkka; Alpo Willman (Bank of Finland, 1988)
Specification of the volume and price equation of Finlands multilateral exports of goods is based on the assumption that Finnish products enjoy only temporary monopoly power. In the context of the whole model this implies that the price of exports of goods as well as short-run marginal costs converge towards a level determined solely by competing foreign prices. The modelling of Finlands bilateral trade is based on the assumption that the value of bilateral exports adjusts to the value of bilateral imports, which, in turn, is determined by Finnish demand for imports from eastern markets. Modelling of the trade in services and imports, excluding imports of oil, fuels and lubricants, is quite conventional: the volume of exports of services and the volumes of imports depend on relevant relative price and activity variables. The modelling of imports of crude oil, fuel and lubricants is based on the assumption that imports of energy are a residual determined by the demand for and the domestic supply of energy.
URN:NBN:fi:bof-201807271734
Keywords: 330